Occupational health and safety issues in the informal economic segment of Pakistan: a survey of construction sites - Ishfaq, Ahmed; Muhammad Zeeshan, Shaukat; Ahmad, Usman; Muhammad Musarrat, Nawaz; Mian Sajid, Nazir (Taylor and Francis Ltd., 2018)
This research covers the current status of occupational health and safety (OHS)-related practices in the informal construction segment of Pakistan. Data were collected, through interviews, from 316 construction sites employing 3577 workers. The results of the study reveal that both employers and workers lack knowledge of OHS laws/standards and no practices of this nature are enacted at these construction sites. Alarmingly, work-related accidents, whenever they happen, are not given due attention and there is no formal injury-report system. The informal construction industry employs a huge portion of the informal workforce, and lack of OHS happens at tremendous human cost. These research findings may thus play their role in strengthening the case for reforms in the sector. This study, if properly utilized, may also enable employers of the sector by increasing their knowledge about OHS practices and, as a result, trying to offer safer environments for their workers. © 2017 Central Institute for Labour Protection–National Research Institute (CIOP-PIB).